KEBUDAYAAN BALI DALAM KONTEKS PENGEMBANGAN PARIWISATA BUDAYA - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Bali which is famous abroad because of its unique and diverse culture cannot be separated from the role of the Balinese language. Balinese is an inseparable cultural root of Bali. Balinese culture includes livelihood systems, equipment systems, social systems, scientific systems, religious systems, art systems, and language systems. Based on the background above, two formulations of problems can be identified, namely: how are the elements of Balinese culture as a supporter of tourism in Bali? and how the relationship of Balinese culture in the effort to develop cultural tourism?Bali's socio-cultural capital that is so unique when compared to other regions in Indonesia, Bali has great potential in the effort to develop cultural tourism which is based on Balinese culture. It can be concluded that Balinese culture in the context of developing cultural tourism is as follows: relating to elements of Balinese culture (religious systems, science, livelihoods, equipment, arts, social organizations, and Balinese language) and some cultural tourism-based development Bali, namely culinary tourism, beach tourism, and mountain nature tourism.In connection with the main socio-cultural capital owned by Bali, the government should; both the central and regional governments, always see the potential of Bali as a tourism development area that is based on Balinese culture. Bali cannot be compared to other regions in Indonesia which have vast demographic areas, which makes it possible to build an economy based on regional breadth. Bali with all its cultural uniqueness, should be built based on its socio-cultural potential, which has been proven by the unique socio-cultural potential, can make Bali as one of the largest tourist destinations in the world.Keywords: Cultural Elements, Socio-Cultural Capital, and Tourism Development